Stability of Organic Carbon Components in Shale: Implications for Carbon Cycle - Basu, Sudeshna; Verchovsky, Alexander B.; Bogush, Anna; Jones, Adrian P.; Jourdan, Anne-Lise (Frontiers in Earth Science, 2019)
Stability and mobility of organic matter in shale is significant from the perspective of carbon cycle. Shale can only be an effective sink provided that the organic carbon present is stable and immobile so that it is not released easily during low temperature geological processes such as burial diagenesis. To examine this, three Jurassic shale samples of known mineralogy and total organic carbon content, with continental source of organic matter, belonging to the Haynesville-Bossier Formation were combusted by incremental heating from temperature of 200 to 1400°C. The samples were analysed for their carbon and nitrogen release profiles, bulk δ13C composition and C/N atomic ratio, based on which, at least four organic carbon components are identified associated with different minerals such as clay, carbonate and silicate. They have different stability depending on their host sites and occurrences relative to the mineral phases and consequently, released at different temperature during combustion. The components identified are denoted as, C1 (organic carbon occurring as free accumulates at the edge or mouth of pore spaces), C-2 (associated with clay minerals, adsorbed or as organomineral nanocomposites; with carbonate minerals, biomineralised and/or occluded) C3-1 (occurring with silicate minerals, biomineralised and/or occluded and C3-2 (graphitized carbon). They show an increasing stability and decreasing mobility from C1 to C3-2. Based on the stability of the different OC components, shale is clearly an efficient sink for the long term C cycle as, except for C1 which forms a very small fraction of the total and is released at temperature ~ 200°C, OC can be efficiently locked in shale surviving conditions of burial diagenesis. C3-2 can be even efficiently retained as a refractory phase under shallow mantle conditions if subducted. It is evident that the association and interaction of the organic matter with the different minerals play an important role in its retention in the shale.